A Yolk Sac Larger Than 5 mm Suggests an Abnormal Fetal Karyotype, Whereas an Absent Embryo Indicates a Normal Fetal Karyotype. (1st November 2017) - Yoneda, Satoshi; Shiozaki, Arihiro; Yoneda, Noriko; Sameshima, Azusa; Ito, Mika; Shima, Tomoko; Nakashima, Akitoshi; Yoshino, Osamu; Kigawa, Mika; Takamori, Ryosuke; Shinagawa, Yasuhiro; Saito, Shigeru
Abstract : Objectives: It is very hard to estimate an abnormal or normal fetal karyotype in miscarriage before surgery. We investigated whether the abnormal fetal karyotype in early miscarriage could be estimated by comprehensive ultrasonographic findings by a multivariate analysis. Methods: One hundred fifty‐one patients with early miscarriage (<12 weeks' gestation) were selected in our hospital. The clinical characteristics were compared between pregnant women carrying a fetus with an abnormal karyotype and those with a normal one, and the size and configuration of the gestational sac, yolk sac, and embryo at diagnosis of early miscarriage were also evaluated. Results: The rate of abnormal fetal karyotypes was 66.2 % (100 of 151). A maternal age older than 35 years (odds ratio, 3.2; 95% confidence interval, 1.4–7.4; P  = .005), yolk sac larger than 5 mm (odds ratio, 6.2; 95% confidence interval, 2.2–22.7, P  < .001), and absent embryo (odds ratio, 0.40; 95% confidence interval, 0.16–0.95; P  = .038) were independent markers for predicting an abnormal fetal karyotype by multiple logistic regression analysis. Conclusions: At the point of early miscarriage diagnosis, a yolk sac larger than 5 mm suggests an abnormal fetal karyotype, whereas an absent embryo indicates a normal fetal karyotype.